Slope stability analysis of rock mass using Rock Mass Rating and Slope Mass Rating - Haryati, Awang; A F, Salmanfarsi; A Z, Misbahuddin; Mohamad Idris, Ali (IOP Publishing Ltd, 2021)
The rapid development in the construction of infrastructure on the hilly terrain has led to excavation of large bodies of rock mass to form cut slopes, resulting in the deformation and reduction in the stability of the rock material. As the slopes were cut more than 10 years ago, it is worried that there should be strength deterioration of the rock slope that could affect the stability of the slope. A study should be carried out to evaluate the recent condition of the slope in terms of its stability and safety after a long period of the exposure. A field study was conducted to collect the discontinuity data and laboratory test for the purpose of stability analysis using the existing stability analysis scheme of Rock Mass Rating (RMR) and Slope Mass Rating (SMR). The study was taken place at an exposed cut slope of a highway in Sri Jaya, Pahang. The objective of this study is to determine and evaluate the stability of the rock cut slope. A classification of the discontinuity parameters such as the strength, Rock Quality Designation (RQD), spacing, aperture, infilling, persistence, weathering, and groundwater have been used to determine the rock mass condition. The classification also need laboratory test for the point load strength (PLT) parameter. The RMR classification showed the rock to be very good condition, while the SMR showed the slope to be completely stable to stable. This study provide a good database in assessing the rock slope condition from time to time for the slope authority management.